2013
DOI: 10.1055/s-0032-1328130
|View full text |Cite
|
Sign up to set email alerts
|

5-Geranyloxy-7-Methoxycoumarin Inhibits Colon Cancer (SW480) Cells Growth by Inducing Apoptosis

Abstract: For the first time, three coumarins were isolated from the hexane extract of limes (Citrus aurantifolia) and purified by flash chromatography. The structures were identified by NMR (1D, 2D) and mass spectral analyses as 5-geranyloxy-7-methoxycoumarin, limettin, and isopimpinellin. These compounds inhibited human colon cancer (SW-480) cell proliferation, with 5-geranyloxy-7-methoxycoumarin showing the highest inhibition activity (67 %) at 25 µM. Suppression of SW480 cell proliferation by 5-geranyloxy-7-methoxyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…The 1 H and 13 C NMR data and literature [15] show that the isolated compound 2 is 4(2,3-dihydrogeranyloxy)-5(4(2,3-dihydrogeranyloxy)phenylbergapten. [16].…”
mentioning
confidence: 85%
“…The 1 H and 13 C NMR data and literature [15] show that the isolated compound 2 is 4(2,3-dihydrogeranyloxy)-5(4(2,3-dihydrogeranyloxy)phenylbergapten. [16].…”
mentioning
confidence: 85%
“…Another important link explored in the study was Ca2+-sensitive PKC exerted inhibitory effects on ERK induced signalling in Nobiletin treated cells (Aoki et al, 2013). Phosphorylated levels of p38 MAPK were also reduced in 5-Geranyloxy-7-methoxycoumarin treated colon cancer (SW480) cells (Patil et al, 2013).…”
Section: Erk1/2 Pathwaymentioning
confidence: 96%
“…5-Geranyloxy-7-methoxycoumarin, isolated from hexane extract of Citrus aurantifolia induced cell cycle arrest at G0/G1 phase in colon cancer (SW480) cells (Patil et al, 2013). Cell cycle arrest was induced in A549 lung cancer cells upon treatment with flavonoids isolated from Korean Citrus aurantium L (Park et al, 2012).…”
Section: Cell Cycle Arrestmentioning
confidence: 99%
“…In another study conducted by Patil et al (2013), the role of coumarins (5-geranyloxy-7-methoxycoumarin, limettin and isopimpinellin) present in Citrus aurantifolia was examined for their antiproliferative actions. In vitro studies on human colon cancer cells (SW480) showed that 5-geranyloxy-7-methoxycoumarin exhibited 67% growth inhibition at a dose of 25 µM.…”
Section: Citrus Limonoids Mechanism Of Anticancer Activity Referencesmentioning
confidence: 99%